Optimal design of engineering systems using MPI-enabled genetic algorithm - Rajan, S. D.; Nguyen, D. T.; Deshpande, M. D.; Harrell, L. (Computer Assisted Methods in Engineering and Science, 2004)
The focus of this paper is on the development and implementation of a genetic algorithm (GA)-based software system using message passing interface (MPI) protocol and library. A customized form of simple GA used in previous research [1-4] is parallelized. This MPI-enabled version is used to find the solution to finite element based design optimization problems. Results show that an almost linear speedup is obtained on homogenous hardware cluster and, with proper reworking of the software, on heterogeneous hardware cluster.